Characterization of Thyroid Nodule by Sonographic Features - Khadka, Hensan; Sharma, Saroj; Ghimire, Ram Kumar; Sayami, Gita (Nepalese Journal of Radiology, 2018)
Introduction: The thyroid is an endocrine gland situated in the infrahyoid compartment of neck in a space outlined by muscle, trachea, esophagus, carotid arteries and jugular veins. Though nodular thyroid disease is relatively common, thyroid cancer is rare and accounts for less than 1% of all malignancies indicating that overwhelming majority of thyroid nodules are benign. The purpose of this study was to assess the sonographic characteristics in a solitary thyroid nodule and predict risk of malignancy. Methods: This prospective study was conducted in a tertiary care hospital in Kathmandu.62 patients with palpable thyroid nodule were evaluated for sonographic characteristics .USG guided FNA for cytopathological examination was then performed. Results: Out of 66 patients, four were subsequently excluded because they didn’t fulfill the inclusion criteria. Of the 62 patients, 47 (75.8%) were females and 15 (24.2%) were males. Among 56 benign nodules, 45 (80.4%) were in females and 11(19.6) were in male. Among 6 malignant nodules, 4(66.7%) were in males and 2 (33.3%) were in females. Result shows 5 malignant nodules (83.3%) were solid where as 1 malignant nodule (16.7%) was complex with solid predominance. All 4 cystic nodules (7.1%) were benign. All complex nodules with predomint cystic components were also benign. One malignant nodule (16.7%) had snow storm type of microcalcification. None of the benign nodules had microcalcification. Nodule having microcalcification was malignant. Findings showed that all malignant nodules (100%) had increased internal vascularity whereas benign nodules were variable in internal vascularity. Conclusion: This study has shown that colloid goiter is the commonest benign diagnosis whereas papillary carcinoma is the commonest malignancy. Malignant nodules are solid or predominantly solid whereas cystic and predominantly cystic nodules are likely to be benign. Macrocalcification and internal vascularity are not reliable to differentiate benign from malignant nodule. However, snowstorm calcification makes a nodule likely to be malignant whereas egg shell calcification is characteristic for benign nodule.